Analysis of factors affecting adoption of mobile banking application in Indonesia: an application of the unified theory of acceptance and use of technology (UTAUT2) - Mufingatun, Mufingatun; Prijanto, Budi; Dutt, Himanshu (BISMA (Bisnis dan Manajemen), 2020)
Information technology has made mobile banking easy, convenient and accessible to 178 million unique mobile subscribers base in Indonesia. Out of this 50 million are smartphone users and collectively about 132 million are internet users . This rising trend has been forcing 120 commercial banks in the country to ramp up their mobile-based banking initiatives. However, in contrast to it, only 50 million have bank accounts out of 250 million Indonesian population size . This poses a few challenges to digital adoption using mobile as medium, especially when a limited number of people have bank accounts and the cost of internet is high due to geographical, infrastructural spread and cost barriers. The purpose of this study is to unearth such factors that have - direct or indirect - influence on consumer acceptance for mobile banking applications. This research model examines 205 respondents from online surveys in Jabodetabek, Indonesia. To conduct this study, we have used Unified Theory of Acceptance and Use of Technology (UTAUT2) model that helps in understanding perceived credibility and perceived self-efficacy variables and their roles in influencing the adoption for m-banking. Data was analysed using Partial Least Square (PLS) method. The findings suggest that performance expectancy, effort expectancy, and social influence have a significant effect on behavioral intention. Performance expectancy is the factor that mostly influences behavior intention. It can also be stated that behavioral intention, facilitating condition and habit all of these have a significant effect on reuse behavior.